Demodulation of non-stationary machine vibration using cycle-time scale - P. KRZYWORZEKA; W. CIOCH (Archives of Acoustics, 2014)
Inner time-scale affects the operation of angle demodulator. Can linear approximation of monotonic variations in carrier-cycle improve the recovery of unknown low-energy signal modulating observable vibration processes? Authors make an attempt to answer using phase-locked loop PLL as demodulator. Simulations conducted for complex phase model indicate potentially vast possibilities of recognizing and selection of information component. Appropriate selection of approximation time-range enables to achieve acceptable RMS value loads and harmonics of rotational speed of outgoing estimates.